PENYIMPANGAN TERHADAP ASAS NON-RETROAKTIF DALAM PERKARA PELANGGARAN HAM BERAT - Rawung, Hendra (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2017)
Indonesia has been criticized by the international community, especially the many actors who are considered responsible for some particularly of the gross violation of human rights that occurred in the past are allowed to live free from prosecution. With regard to the occurrence of the gross violations of human rights in the past there is a legal breakthrough in an effort to uncover and resolve cases the gross violations of human rights, namely the demise of a provision enacted criminal known as retroactive. It is stipulated in Article 43 Paragraph (1) Law No. 26 of 2000 concerning Human Rights Court. Efforts to impose a retroactive principle on one hand has been controversial because it is considered contrary to the principle of non retroactivity which is a manifestation of the principle of legality, which in principle is a provision that prohibits the enactment of the statute retroactively. But the other side of the principle of non retroactivity is also considered to be protecting the perpetrators to be free from prosecution and sentencing. Kata Kunci: Penyimpangan, Asas, Non-Retroaktif, Pelanggaran, HAM.